10z-2+9z-3-z=

Simple and best practice solution for 10z-2+9z-3-z= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10z-2+9z-3-z= equation:


Simplifying
10z + -2 + 9z + -3 + -1z = 0

Reorder the terms:
-2 + -3 + 10z + 9z + -1z = 0

Combine like terms: -2 + -3 = -5
-5 + 10z + 9z + -1z = 0

Combine like terms: 10z + 9z = 19z
-5 + 19z + -1z = 0

Combine like terms: 19z + -1z = 18z
-5 + 18z = 0

Solving
-5 + 18z = 0

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 5 + 18z = 0 + 5

Combine like terms: -5 + 5 = 0
0 + 18z = 0 + 5
18z = 0 + 5

Combine like terms: 0 + 5 = 5
18z = 5

Divide each side by '18'.
z = 0.2777777778

Simplifying
z = 0.2777777778

See similar equations:

| -4=2/5*w | | X^2+2x+6=78 | | -6x+17=47 | | 4/7(4760) | | x^3+12x^2-55x+14=7 | | 1/9x2y-3=3 | | f(x-9)=3x+1 | | -5/8*u=-25 | | (35)1/7 | | 3y^2+8y-51=0 | | 6(n-11)=4.4n-2 | | 4(x+2)=24x-3 | | 2/12(12) | | 2x^2+2x-xy-y= | | 17x+2y=18 | | 3x+20+10x-15=90 | | y=200x+1200 | | .02x+.15=.43 | | 3s-7-s+1=6 | | 3x-28=20+6x | | 4x^3-8x^2=48x | | 16/39(3/10) | | 4.13x+24.78=49.56 | | ax-b=dx-c | | 64+16k+k^2= | | 19/57 | | -6x-117=3x+153 | | 4/2x-3=3/x-2 | | 2x+y+5-3= | | -143+3x=-6x+118 | | 1/4y=-15 | | 36=10/h |

Equations solver categories